The Effect of Workload and Fatigue on Employee Occupational Health and Safety: A Literature Review - Nurdiyanti, Putriayu; Widodo Hariyono; Heni Trisnowati (Sean Institute, 2025)
Workload is a task used to measure an employee's activity and achievement, while work fatigue also often occurs in employees who are commonly referred to as high-touch jobs that involve a lot of face-to-face. In occupational health and safety (K3), namely ensuring the health and safety of employees who are working and preventing unwanted work accidents. This literature review is to find out about the effect of workload and fatigue on occupational health and safety in employees. In this study, an analysis or approach was carried out by means of a literature review. By searching for various relevant sources using the observation method through the Google Scholar, PubMed, and Garuda platforms. Then in the search criteria for this journal there are two types of access, namely inclusion and exclusion, in this literature review using the mixed case control or cross-sectional method. The results of the journal obtained 13 articles explaining that the effect of workload and fatigue on occupational health and safety has significant results or has an effect on employees. The effect of workload and fatigue provides significant results on occupational health and safety (K3) in employees, so this study will provide further intervention to find out how many employees experience accidents due to large workloads and the resulting fatigue.